Liturgy, architecture, and sacred places in Anglo-Saxon England - Gittos, Helen (Oxford Oxford University Press, 2013)
Church rituals were a familiar feature of life throughout much of the Anglo-Saxon period. This book examines ceremonies for the consecration of churches and cemeteries, processional feasts like Candlemas, Palm Sunday, and Rogationtide, as well as personal rituals such as baptisms and funerals. Drawing on little-known surviving liturgical sources as well as other written evidence, archaeology, and architecture, it considers the architectural context in which such rites were performed.
Includes bibliographical references and index.
Keywords: Electronic books; Liturgics -- England -- History -- To 1500.; Liturgy and architecture -- England -- History -- To 1500.; Sacred space -- England -- History -- To 1500.; Anglo-Saxons -- Rites and ceremonies